Health-related quality of life of tuberculosis Patients in Bagdad and Socio-demographic Factors Associated with Multiple Drug Resistant Tuberculosis (MDR TB) - Marzook, Ahmed Abed (Diyala Journal of Medicine, 2019)
Background: Tuberculosis is a highly infectious disease that primarily affects the lungs. It can also affect other organs. TB was once called “consumption.” It is the world’s second-most fatal infectious agent, after HIV/AIDS Objective: To evaluate the effect of sodium nitrate, vitamin E and vitamin C administration on liver enzymes, alanine transaminase, aspartate transaminase and alkaline phosphatase. This research aimed to study the effect of tuberculosis (TB) on quality (QOl) of life of MDR and non DR TB patients, it also to explore any possible association between getting MDR TB and socio- demographic variables Materials and Methods: A cross-sectional study was conducted in Chest and Respiratory Diseases Center (CRDC) –Baghdad during 2015. The World Health Organizations Quality of Life Assessment (WHOHQL-BREF) was used to asses QOL of 50 MDR and 50 Non DR sputum positive pulmonary TB patients. Socio-demographic variables were studied. SPSS V. 22, was used in statistical analysis, Chi-square and Mann-Whitney-U tests were used to test significance of differences, PV≤ 0.05 was considered significant. Results: The mean age was 43.46 ± 14.8 and 37 ± 16.16 for MDR-TB and non-DR-TB respectively. The age difference was significant (p=0.048). Males constitute a majority in both groups (DR-TB 64% and non-DR-TB 59%). Smoking was higher in DR-TB than non-DR-TB (57% and 38% respectively) and difference was significant (P =0 .016). Significant differences between DR-TB and non-DR-TB in global QOL, global health, physical, psychological, social and environmental domains (P=0.004, 0.014, 0.001, .0019, 0.001 and 0.001 respectively). Conclusion: Patients with MDR-TB had lower mean scores than non-DR-TB for overall HRQOL domains. There is association between getting MDR TB and being older in age, lower educational level, smokers and being jobless.